PROBLEMATIKA WAKTU SHALAT GERHANA YANG TERTUTUP MENDUNG - Mahaendra, Ikhsan (Al-Maslahah : Jurnal Ilmu Syariah, 2023)
The Qur'an and hadith have explained eclipses, but not completely. The eclipse prayer can be performed if the eclipse is visible and its area is crossed by it, according to the underlying hadith. But not all days are sunny. There are times when clouds block the cloudy weather, so the eclipse cannot be seen. Ibnu Hajar al-Haitami is one of the scholars who discusses this. He stated that there were differences of opinion regarding the Eclipse Prayer. Therefore, the author provides an explanation of the laws of eclipse prayer, especially those related to how to perform the Sunnah eclipse prayer if the weather around the eclipse is cloudy or vice versa. In terms of conclusions, the scholars and Imams of the four schools of thought agree that performing the eclipse prayer is a sunnah mukaad and is prioritized to be done in congregation. However, priests differ on how to do it in congregation if a solar eclipse occurs, while a lunar eclipse is done individually. Ibnu Hajar Al-Haitami agrees with Imam Syafi'i regarding the law of carrying out the Eclipse Prayer, procedures, times, and other matters. He said that if the eclipse occurs before it is cloudy, then the eclipse prayer is still performed, but if it is cloudy from the beginning to the end of the eclipse, then it is not recommended to do it.